Environmental Health Evaluation for Jatinegara Apartment from the Perception of Kampung Pulo Displaced People - Ayu Puspito Sari, Deffi; Madonna, Sandra; Fitriani, Amalia (International Journal of Engineering and Technology, 2018)
Limited land availability and population growth resulted in the emergence of illegal housing and slums in Jakarta. Kampung Pulo area in East Jakarta is one of the regions occupied by the illegal structures and slums. To overcome the problem, the Government of DKI Jakarta built a simple rental apartment (Rusunawa) used for relocation of Kampung Pulo community. The aims of this research are to study the socio-economic condition of Rusunawa residents, the environmental health of Rusunawa Jatinegara compared to Kampung Pulo, and to know the influence of socio-economic status to the opinion of displaced people. Using descriptive method, scoring, analysis correlation and multiple regression (SPSS 16.0). The results show that majority of the education level of residents in Rusunawa Jatinegara is dominantly junior and senior high school, whereas the majority of their income is high. The parameter according to the public perception which is far better in Rusunawa compared within Kampung Pulo that is flood and animal transmitting diseases such as rats and flies. Partially the level of education affects the public perception while the income level does not change the public perception of the comparison between the environmental health in Rusunawa Jatinegara and the environmental health in Kampung Pulo. Simultaneously the level of the education and the income has positive impact to the public perception on the comparison of the environmental health in Rusunawa Jatinegara and the environmental health in kampong Pulo. Interestingly, apart from better environment health standar by Ministry of Health, according to the society's perception, 5 out of 20 parameters of the environmental health in Rusunawa is worse when it is compared to Kampung Pulo, the settings are water quality, rooms layout, lighting, sleeping area, and house building area.Â Â